Optical and structural properties of PEO-like plasma polymers - Mota, Rogério Pinto [UNESP]; Bigansolli, A. R.; Antunes, E. F.; Rangel, E. C.; Da Cruz, N. C.; Honda, R. Y.; Algatti, M. A.; Aramaki, E. A.; Kayama, M. E. (Taylor & Francis Ltd, 2002)
This paper deals with the study of optical, structural and biocompatible properties of PEO-like plasma polymerized films resulting from RF excited diethylene glycol dimethyl ether (CH3O(CH2CH2O)(2)CH3 diglyme) glow discharges. The study was carried out using visible-ultraviolet and FTIR spectroscopies and contact angle measurements. FTIR spectra of plasma polymerized diglyme showed a stronger presence of ethylene glycol groups in film structure for lower RF power levels. The contact angle measurements for water revealed an increasing from 30degrees to 62,5degrees when the RF power was varied from 2 to 45 W, indicating the decreasing of the hydrophilic character of diglyme films with the increasing of RF power. This trend is in agreement with FTIR results. The data from visible-ultraviolet reflectance and transmittance spectra revealed alterations on optical properties of plasma polymerized diglyme films. The film's optical gap varied from 3.8 to 3 eV for RF power running from 5 to 45 W.
Keywords: optical-gap; contact-angle; diglyme-plasmas; diglyme-coatings; plasma-polymers